Investigating the correlation between phenotypes, adrenal transcriptome, and serum metabolism in laying ducks exhibiting varying behaviours under the same stressor - H.X. Sun; R.B. Guo; T.T. Gu; Y.B. Zong; W.W. Xu; L. Chen; Y. Tian; G.Q. Li; L.Z. Lu; T. Zeng (Animal)
Laying ducks in cage environments face various stressors, including the fear of novelty, which negatively affects their behaviour and performance. The reasons behind the variation in behaviour under identical stress conditions are not well understood. This study investigated how different behaviours affect production performance, immune response, antioxidant capabilities, adrenal gene expression, and serum metabolite profiles in caged laying ducks subjected to the same stressor. Overall, 42-week-old laying ducks (N = 300) were selected, fed for 60 days, and simultaneously underwent behavioural tests. Based on their behavioural responses, 24 ducks were chosen and categorised into two groups: high-active avoidance (HAA) and low-active avoidance (LAA). The study utilised phenotypic, genetic, and metabolomic analyses, coupled with bioinformatics, to identify crucial biological processes, genes, and metabolites. The results indicated that ΔW (BW gain) and average daily egg weight (ADEW) were significantly lower in the HAA group compared to the LAA group (P < 0.05). By contrast, the feed-to-egg ratio was higher in the HAA group than in the LAA group (P < 0.05). Levels of serum immunoglobulin A, total antioxidant capacity, and the activities of enzymes like superoxide dismutase and catalase (CAT) were significantly lower in the HAA than in the LAA group (P < 0.05), whereas serum ACTH levels were significantly higher in HAA than in the LAA group (P < 0.05). The adrenal transcriptome analysis revealed 148 differentially expressed genes in the HAA group, with 97 up-regulated and 51 down-regulated. Moreover, enrichment analysis highlighted significant differences in two metabolic pathways: neuroactive ligand-receptor interaction and oxidative phosphorylation (P < 0.05). Serum metabolomics identified 11 differentially accumulated metabolites between the groups, with variations in up and down-regulation. Integrative analysis of phenotype, transcriptome, and metabolome data showed a strong correlation between the exosome component 3 (EXOSC3) gene, phenotypic traits, and differential metabolites. Thus, we deduced that the differences in average daily egg weight among ducks could be linked to variations in gabapentin and EXOSC3 gene expressions, affecting serum CAT levels.